Application of Range of Motion (ROM) Exercise in the Elderly with Muscle and Joint Weakness - Eva Susanti; Jawiyah Jawiyah (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
About 10% of the elderly who live at home complain of some limitations in mobility, while the elderly who live in certain institutions are more than 90% dependent on at least one daily activity. The results of research conducted by Anna Hudakova and Anna Hornakova regarding mobility and quality of life in elderly and geriatric patients found that 16% had low mobility, 32% had moderate mobility and 52% had high mobility in geriatric patients with a sample of 321 respondents. The method used is the delivery of material ( counseling) and training by competent resource persons. Through community service activities, efforts are made to improve the degree of public health. Effective ROM (Range Of Motion) counseling and training activities for the elderly can improve the health and independence of the elderly to meet the needs of daily activities in an effort to support government programs namely the Healthy Living Community Movement (GERMAS), especially the elderly community.